COVID-19 Pandemic: Impact on Net Interest Margin of Indonesian Banking Industry - Hidayat, Ariodillah; Liliana; Gustriani; Shodrokova, Xenaneira; Hakim, Muhammad Nur (Faculty of Economics, Universitas Sriwijaya, 2024)
The study explores factors affecting Net Interest Margins (NIM) in Indonesia's Core Capital Bank Groups. Using data from Jan 2021 to Mar 2022 and the Error Correction Model, it finds negative short-term correlations between BOPO and LDR with NIM in KBMI 1 and positive long-term correlations with BI Rate. KBMI 2 exhibits negative short-term correlations between inflation and LDR with NIM. KBMI 3 shows negative short-term correlations with Covid-19, LDR, and BOPO with NIM. KBMI 4 experiences negative impacts from BOPO, Covid-19, and LDR on NIM in both short and long terms. The study emphasizes the importance of managing operational costs and credit distribution for NIM stability in the short term and highlights the significant influence of Bank Indonesia's benchmark interest rate policy on NIM in the long term, requiring careful adjustments to prevent excessive fluctuations.